Effect of metal doping on carbon monoxide adsorption on phosphorene: A first-principles study. (December 2018) - Sun, Xiaolong; Luan, Shan; Shen, Haiyun; Lei, Shuangying
Abstract: The effects of metal dopings on the carbon monoxide (CO) adsorption of phosphorene were investigated by the first-principles calculations. Base on the analysis of CO adsorption energy, Barder charge and density of states, it is found that six metal (Li, Al, Ni, Pd, Pt, and Au) dopings can improve the adsorption strength of CO. After CO adsorption, Li and Al doped phosphorene (bP-Li and bP-Al) undergo the indirect-to-direct bandgap transitions, while Ni and Au doped phosphorene (bP-Ni and bP-Au) undergo the magnetic-to-nonmagnetic transitions. These results imply that these six metal doped phosphorenes could be candidate materials for removing and detecting toxic CO. Highlights: Six metals (Li, Al, Ni, Pd, Pt, and Ni) doping significantly enhanced adsorption strength of CO on phosphorene. For the bP-Ni system, the adsorption energy of CO can be up to 1.16 eV. For the bP-Al system, it presents the smallest geometrical deformation after CO adsorption. bP-Li and bP-Al experience indirect-to-direct bandgap transitions after CO adsorption. bP-Ni and bP-Au undergo magnetic-to-nonmagnetic transitions after CO adsorption.